ANALISIS PENGELOLAAN PENYIMPANAN BAHAN BAKU MENTAH RESTORAN THE KOREAN EATERY DI BALIKPAPAN - Setyawati, Nur Falah; Maslina, Maslina; Apiliani, Irma Wulan (Program Studi Kesehatan dan Keselamatan Kerja, 2021)
Good raw and clean raw material storage and good recording from restaurant workers is a standard of the Indonesian health minister's regulation on food hygiene and sanitation services. This research is a combination of qualitative and quantitative research. The number of samples in this study as much as 2 samples. Sampling of this sample data through interviews and observation. Data analysis is used to calculate the percentage of observations. The results of this study show that 80% of the standard food management in Permenkes RI No.1096 / Menkes / per / VI / 2011. And other results from this research is showing 20% ​​where the management of raw material storage in the restaurant is not in accordance with Permenkes. These mismatches because no Activities of first in First out and rooms that are too humid. The results showed that 80% according to Permenkes and 20% are not suitable is the absence of first in first out and humid room temperature Keywords : Hygiene , Sanitasi, Food